Rethinking Residency Conferences in the Era of COVID‐19. Issue 3 (27th April 2020) - Gottlieb, Michael; Landry, Adaira; Egan, Daniel J.; Shappell, Eric; Bailitz, John; Horowitz, Russ; Fix, Megan
Abstract: The COVID‐19 pandemic requires a substantial change to the traditional approach to conference didactics. Switching to a virtual medium for conference sessions presents several challenges, particularly with regard to aspects that rely heavily on in‐person components (e.g., simulation, ultrasound). This paper will discuss the challenges and strategies to address them for conference planning in the era of COVID‐19.